2013
DOI: 10.1176/appi.ajp.2012.12010014
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Changes in Sustained Fronto-Striatal Connectivity and Positive Affect in Major Depression Resulting From Antidepressant Treatment

Abstract: Objective Deficits in positive affect and their neural bases have been associated with major depression. However, whether reductions in positive affect result solely from an overall reduction in nucleus accumbens activity and fronto-striatal connectivity or the additional inability to sustain engagement over time of this network is unknown. Accordingly, we sought to determine whether treatment-induced changes in the ability to sustain nucleus accumbens activity and fronto-striatal connectivity during the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 43 publications
5
104
1
Order By: Relevance
“…Therefore, we can only speculate that a more normative pattern of pre-treatment caudate-dACC connectivity may be associated with larger and global clinical improvement. Further highlighting the role of these neural pathways in clinical course, treatment-induced normalization of fronto-striatal functional connectivity was found to positively correlate with increases in positive affect (Heller et al 2013). Critically, clinical improvement was achieved through either Venlafaxine or Fluoxetine, suggesting that the mechanism of action fostering improvements in positive affect and fronto-striatal connectivity did not differ between the two antidepressants (Heller et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we can only speculate that a more normative pattern of pre-treatment caudate-dACC connectivity may be associated with larger and global clinical improvement. Further highlighting the role of these neural pathways in clinical course, treatment-induced normalization of fronto-striatal functional connectivity was found to positively correlate with increases in positive affect (Heller et al 2013). Critically, clinical improvement was achieved through either Venlafaxine or Fluoxetine, suggesting that the mechanism of action fostering improvements in positive affect and fronto-striatal connectivity did not differ between the two antidepressants (Heller et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Further highlighting the role of these neural pathways in clinical course, treatment-induced normalization of fronto-striatal functional connectivity was found to positively correlate with increases in positive affect (Heller et al 2013). Critically, clinical improvement was achieved through either Venlafaxine or Fluoxetine, suggesting that the mechanism of action fostering improvements in positive affect and fronto-striatal connectivity did not differ between the two antidepressants (Heller et al 2013). Similarly, a recent meta-analysis indicated that increased pre-treatment ACC and striatum activation is a robust predictor of positive response to both pharmacological and behavioral treatment in MDD (Fu et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…SZ, Schizophrenia; MDD, major depressive disorder. subcortical structures in MDD (Heller et al 2013;Strigo et al 2013). While these increased levels of connectivity are observed in detailed studies, it is possible that the dominant negative symptoms of MDD mask clinical indications of greater inter-hemispheric connectivity.…”
Section: Biological Significancementioning
confidence: 96%
“…Among others, these include age of onset of initial depressive episode, number of previous depressive episodes [62], duration of depressive illness [63,64], existence of early childhood trauma [65], and features of emotional dynamics [66][67][68][69], etc. While some studies have indeed controlled for (or specifically examined) such features, it is possible that such individual differences will account for variability (and lack of replication) across studies and help the field better understand the course of the illness.…”
Section: Future Directionsmentioning
confidence: 99%